Coping styles in youth exposed to maltreatment: Longitudinal patterns reported by youth in foster care. (August 2017) - Jackson, Yo; Huffhines, Lindsay; Stone, Katie J.; Fleming, Kandace; Gabrielli, Joy
Abstract: Coping styles in youth living in foster care with a history of maltreatment were examined to determine the nature and stability of self-reported coping behavior over time. Participants included 542 (time 1), 377 (time 2), and 299 (time 3) youth ages 8–22 years (M = 13.28 years, SD = 3.04). Using the Behavioral Inventory of Strategic Control, a dimensional, continuous measure of coping, across four possible coping styles endorsed in reference to specific potentially stressful situations, the results indicated that direct action coping was the most frequently endorsed or preferred style for more than 50% of the sample at each time point. A number of youth endorsed using more than one coping style, indicating some flexibility in the approach to coping when problems occur. Although most youth endorsed a preferred style, coping style endorsed did vary somewhat over time. The coping style endorsed also varied depending on the type of problem referenced, but no statistically significant differences were noted across situations, including social, academic, general, and foster-specific situations. Effects for age were also examined and the results indicated no significant differences across the age range for type of coping most commonly endorsed. The present study is the first large-scale, longitudinal assessment of coping styles in youth in foster care and the results suggest that coping is not a simple, categorical-only construct and the implications for the endorsement of the direct approach for youth in foster care along with the other findings are discussed.